Instagram "Jelajah Maumere" as an Information Delivery Media for Cultural Promotion at the Tourism and Culture Office of Sikka Regency. - Oktavia, Maria; Mustafa, Intan; Sedu, Viktor Ariestyan; Kedoh, Lodowik N. (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2025)
ABSTRACTThis article discusses the role of the Instagram account "Jelajah Maumere" as an information platform for promoting culture in Sikka Regency. The account was initiated by the Sikka Regency Tourism and Culture Office as an effort to introduce local cultural richness to a broader audience (tourist information center). Using a qualitative approach, this study analyzes content, user interactions, and the impact of the promotion. The results show that "Jelajah Maumere" has successfully enhanced the visibility of local culture and serves as an effective communication tool between the government and the community.